Imidazole-loaded covalent organic framework composite material as well as preparation method and application thereof
By loading imidazole into the covalent organic framework material DL229, a covalent organic framework composite material with imidazole load was prepared, which solved the problems of difficulty in material preparation and slow iodine adsorption in the prior art, and achieved efficient and fast gaseous iodine adsorption and simplified preparation process.
Patent Information
- Application Number
- CN202411305200.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
The existing covalent organic framework materials have difficulty in synthesis of monomers, require strict inert atmosphere and high reaction temperature in preparation and application, and the kinetics of iodine adsorption are slow, which limits large-scale preparation and practical application.
By loading the imidazole into the covalent organic framework material DL229, a covalent organic framework composite material supported by imidazole was prepared, and rapid iodine adsorption was achieved using its high specific surface area and open pore structure, simplifying the preparation process.
It realizes efficient gaseous iodine adsorption, simplifies the preparation process, facilitates large-scale production and practical application, and significantly improves the iodine adsorption capacity and rate.
Smart Images

Figure CN119176921A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of environmental science, material science and synthesis technology, and in particular to a covalent organic framework composite material loaded with imidazole and a preparation method and application thereof. Background Art
[0002] Radioactive iodine is an extremely important pollutant in gaseous radioactive nuclear waste due to its volatility, biocompatibility and high mobility. Once it leaks into the environment, it will cause great harm. Therefore, the research and development of efficient iodine adsorption materials is of great significance.
[0003] Solid phase adsorption is the most commonly used method for enriching and storing radioactive gas iodine and has been widely studied and applied. Covalent organic framework (COF) materials are a new type of crystalline porous polymer materials. Due to their highly flexible molecular designability and pore structure controllability, they have great research value and application prospects in the design and preparation of gaseous iodine adsorption materials. However, in existing studies, the use of COF materials for the uptake of gaseous iodine has the following problems: the monomers used are difficult to synthesize, the preparation of the target COF material requires a strict inert atmosphere and a high reaction temperature, the adsorption kinetics of iodine are slow, and it is not conducive to large-scale preparation and practical application. Summary of the invention
[0004] The purpose of the present invention is to provide a covalent organic framework composite material loaded with imidazole, a preparation method and an application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The present invention provides a method for preparing a covalent organic framework composite material loaded with imidazole, comprising the following steps:
[0007] The imidazole is loaded by using the covalent organic framework material DL229 to obtain the imidazole loaded covalent organic framework composite material.
[0008] As a further preferred embodiment of the present invention, the mass ratio of the covalent organic framework material to imidazole is (0.8-0.2):1.
[0009] As a further preferred embodiment of the present invention, the load temperature is 120° C.; the load time is 24-72 hours.
[0010] In the covalent organic framework composite material loaded with imidazole prepared by the invention, the imidazole exists between the gaps of the covalent organic framework material.
[0011] As a further preferred embodiment of the present invention, the covalent organic framework material DL229 is obtained by reacting 1,3,5,7-tetrakis(4-aminophenyl)adamantane and terephthalaldehyde as monomers at 100°C.
[0012] As a further preference of the present invention, the reaction time is 1-3 days.
[0013] As a further preferred embodiment of the present invention, the molar ratio of 1,3,5,7-tetrakis(4-aminophenyl)adamantane (TAA) to terephthalaldehyde (TA) is 9:1.
[0014] The structure of the monomer 1,3,5,7-tetrakis(4-aminophenyl)adamantane is as follows:
[0015]
[0016] The structure of terephthalaldehyde is as follows:
[0017]
[0018] The structural formula of the covalent organic framework material DL229 is as follows:
[0019]
[0020] The more specific preparation method of the present invention is as follows:
[0021] The organic monomer 1,3,5,7-tetrakis(4-aminophenyl)adamantane and terephthalaldehyde are mixed in a molar ratio, ground, and placed in a heat-resistant glass tube, followed by the addition of 1,2-dichlorobenzene and acetic acid solution. (Preferably, the concentration of the acetic acid solution is 6 mol / L, and the volume ratio of 1,2-dichlorobenzene to the acetic acid solution is 3:1.)
[0022] The heat-resistant glass tube was frozen in liquid nitrogen for 5-20 minutes, then vacuumed in the frozen state, and then refilled with nitrogen. After repeating the operation several times, the heat-resistant glass tube was sealed with a hydrogen-oxygen flame in a vacuum state. The sealed heat-resistant glass tube was placed at 100°C for reaction for 3 days, the obtained block solid was ground, and washed with N,N-dimethylformamide and tetrahydrofuran in turn, dried at room temperature, and vacuum dried at 100-150°C for 6 hours to obtain an orange-yellow powder, which is DL229.
[0023] The prepared DL229 was soaked in tetrahydrofuran for 24 h, filtered and vacuumed at 150 °C for 2 h, the pre-weighed open vial containing DL229 was placed in a larger sealed glass bottle containing imidazole, sealed and heated in an oven at 120 °C for 72 h, and cooled to room temperature to obtain an imidazole-loaded covalent organic framework composite material (Im@COF material).
[0024] The present invention also provides a covalent organic framework composite material loaded with imidazole prepared by the preparation method.
[0025] The present invention further provides the use of the above-mentioned imidazole-loaded covalent organic framework composite material as an iodine adsorbent.
[0026] The imidazole-loaded covalent organic framework composite material of the present invention is more preferably used as an adsorbent for gaseous iodine or methyl iodide.
[0027] The present invention discloses the following technical effects:
[0028] The present invention utilizes the COF material DL229 to load imidazole rich in nitrogen atoms to obtain a composite COF material. The composite COF material has a high specific surface area and an open pore structure. The nitrogen-rich structure and the electron-rich π-π conjugated system can provide effective binding sites for the adsorption of iodine. At the same time, the presence of a large number of nitrogen atoms can ensure the material's ability to adsorb iodine.
[0029] The preparation method of the composite COF material of the present invention is simple, the reaction conditions are mild, and the gaseous iodine can be quickly adsorbed, which is convenient for large-scale preparation and practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The figure is the powder X-ray diffraction (PXRD) pattern of DL229.
[0032] Figure 2 This is the Fourier transform infrared spectrum (FTIR) test chart of DL229.
[0033] Figure 3 This is the loading amount of imidazole on COF material DL229 and activated carbon.
[0034] Figure 4 XRD of DL229 and four kinds of Im@DL229 materials prepared in Examples 1-4.
[0035] Figure 5 FTIR spectral analysis of imidazole, DL229 and three Im@DL229 materials prepared in Examples 1-3.
[0036] Figure 6 Iodine adsorption performance of four Im@DL229 materials prepared in Examples 1-4.
[0037] Figure 7 The iodine adsorption performance of DL229 and Im_0.075@DL229 prepared in Example 3.
[0038] Figure 8 These are the experimental results of iodine adsorption kinetics of DL229 and Im_0.075@DL229 prepared in Example 3.
[0039] Fig. 9 The iodine retention test results of DL229 and four Im@DL229 materials prepared in Examples 1-4 in a closed environment (room temperature conditions).
[0040] Fig.10 The iodine retention test results of DL229 and four Im@DL229 materials prepared in Examples 1-4 in a semi-closed environment (room temperature conditions).
[0041] Fig.11 The iodine retention test results of DL229 and four Im@DL229 materials prepared in Examples 1-4 in an open environment (room temperature conditions).
[0042] Fig.12 This is the iodine analysis curve (75°C) of Im_0.075@DL229 synthesized in Example 3.
[0043] Fig.13 These are the experimental results of five consecutive static iodine adsorption cycles of Im_0.075@DL229 and DL229 synthesized in Example 3.
[0044] Fig.14 These are the experimental results of CH3I adsorption performance of Im_0.075@DL229 and DL229 synthesized in Example 3.
[0045] Fig.15 These are the static CH3I adsorption kinetic experimental results (75°C) of Im_0.075@DL229 synthesized in Example 3.
[0046] Fig.16 This is a static CH3I cyclic adsorption experiment of Im_0.075@DL229 synthesized in Example 3.
[0047] Fig.17 These are the CH3I retention experimental results (room temperature conditions) of Im_0.075@DL229 synthesized in Example 3 in three different environments (closed environment, semi-closed environment, and open environment). DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0052] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0053] The preparation of the Im@COF material of the present invention is described below in conjunction with specific examples:
[0054] Example 1
[0055] The organic monomer 1,3,5,7-tetrakis(4-aminophenyl)adamantane (1.8mmol, 0.10g) and terephthalaldehyde (0.2mmol, 0.05g) were fully mixed and ground, and then loaded into a heat-resistant glass tube. Subsequently, 1,2-dichlorobenzene and acetic acid solution (6mol / L) were added to the glass tube in sequence, wherein the volume ratio of 1,2-dichlorobenzene to acetic acid solution was 3:1, and a total of 1.5mL was added.
[0056] The heat-resistant glass tube was frozen in liquid nitrogen for 15 minutes, then vacuumed in a frozen state, and then refilled with nitrogen. After repeating the operation three times, the heat-resistant glass tube was sealed with a hydrogen-oxygen flame in a vacuum state. The sealed heat-resistant glass tube was placed at 100°C for 3 days, and the obtained block solid was ground and washed with N,N-dimethylformamide and tetrahydrofuran in turn, dried at room temperature, and vacuum dried at 120°C for 6 hours to obtain an orange-yellow powder, which was marked as DL229.
[0057] The prepared DL229 was soaked in tetrahydrofuran for 24 h, filtered and vacuumed at 150 ° C for 2 h, and a pre-weighed open vial (20 mL) containing 20 mg DL229 was placed in a larger sealed glass bottle (100 mL) containing 25 mg imidazole. After sealing, it was heated in an oven at 120 ° C for 72 h, cooled to room temperature, and the prepared product was marked as Im_0.025@DL229.
[0058] Figure 1 The figure is the powder X-ray diffraction (PXRD) pattern of DL229. It can be seen that the PXRD pattern of DL229 has a strong peak at 5.44 and other small peaks at 11.06, 16.66, 19, and 19.62, which is consistent with the theoretically simulated structural PXRD pattern in the literature.
[0059] Figure 2 The Fourier transform infrared spectrum (FTIR) test diagram of DL229 shows that its C=O group and NH2 group disappear. The existence of C=N stretching vibration bond indicates that the Schiff base reaction forms an imine bond.
[0060] Example 2
[0061] The only difference from Example 1 is that the amount of imidazole added to the 100 mL sealed glass bottle is 50 mg. The prepared product is marked as Im_0.050@DL229.
[0062] Example 3
[0063] The only difference from Example 1 is that the amount of imidazole added to the 100 mL sealed glass bottle is 75 mg. The prepared product is marked as Im_0.075@DL229.
[0064] Example 4
[0065] The only difference from Example 1 is that the amount of imidazole added to the 100 mL sealed glass bottle is 100 mg. The prepared product is marked as Im_0.100@DL229.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that the imidazole is loaded with activated carbon (AC) equal to that of DL229:
[0068] The activated carbon was soaked in tetrahydrofuran for 24 h, filtered and vacuumed at 150 ° C for 2 h, and a pre-weighed vial (20 mL) containing 20 mg of active material was placed in a larger sealed glass bottle (100 mL) containing 25 mg of imidazole. After sealing, it was heated in an oven at 120 ° C for 72 h and cooled to room temperature to obtain activated carbon loaded with imidazole.
[0069] Comparative Example 2
[0070] The difference from Example 2 is that the imidazole is loaded with activated carbon (AC) equal to that of DL229. The preparation method is the same as that of Comparative Example 1.
[0071] Comparative Example 3
[0072] The difference from Example 3 is that the imidazole is loaded with activated carbon (AC) equal to that of DL229. The preparation method is the same as that of Comparative Example 1.
[0073] Comparative Example 4
[0074] The difference from Example 4 is that the imidazole is loaded with activated carbon (AC) equal to that of DL229. The preparation method is the same as that of Comparative Example 1.
[0075] The loading amount of imidazole on COF material DL229 and activated carbon is as follows Figure 3 As shown. Figure 3 It can be seen that when the amount of imidazole added is 75 mg, the imidazole loading of the COF material reaches the maximum value, and the corresponding product is Im_0.075@DL229 synthesized in Example 3, and the imidazole loading energy of the COF material DL229 is much higher than that of activated carbon.
[0076] Figure 4 XRD of DL229 and four kinds of Im@DL229 materials prepared in Examples 1-4. It can be seen that the PXRD peaks of the four kinds of Im@DL229 materials synthesized in Examples 1-4 all disappeared, which may be due to the increase in pore occupancy and the formation of charge transfer complexes in the network, indicating that the permeation structure of the Im@DL229 material has become disordered and aggregated. With the increase of imidazole loading, the imidazole diffraction peaks appeared in the samples Im_0.050@DL229 and Im_0.075@DL229 synthesized in Examples 2 and 3, and gradually became obvious.
[0077] Figure 5 FTIR spectra of imidazole, DL229 and Im@DL229 prepared in Examples 1-3. The characteristic peaks of CN of the three samples loaded with imidazole appear at 1323, 1100 and 1065 cm-1 At 1259, 935, 892, 658, 617 cm -1 The imidazole peak that appears at the position of the imidazole can prove that the imidazole loading is successful.
[0078] Effect verification example 1: Static iodine vapor adsorption experiment
[0079] (1) I2 adsorption experiment
[0080] An open glass vial (20 mL) containing Im@COF was placed in a glass vial (100 mL) containing solid iodine, sealed and heated at 75°C. After a certain period of time, the sample bottle was cooled to room temperature and weighed, and then placed back into the iodine-containing bottle for continued adsorption until the weight of the sample bottle reached equilibrium, that is, the maximum iodine capture capacity was achieved.
[0081] Iodine absorption capacity is calculated by weight method: W = (m t -m0) / m×100%, where W is the iodine absorption capacity; m0 is the original weight of the sample bottle, g; m t is the weight of the sample bottle after iodine vapor adsorption, g; m is the weight of the COF sample, g.
[0082] (2) CH3I adsorption experiment
[0083] An open glass vial (20 mL) containing Im@COF was placed in a glass vial (100 mL) containing methyl iodide (CH3I), sealed and heated at 75°C. After a certain period of time, the sample bottle was cooled to room temperature and weighed, and then placed back into the iodine-containing bottle to continue adsorption until the weight of the sample bottle reached equilibrium, that is, the maximum CH3I capture capacity was achieved. The absorption capacity calculation method is consistent with the I2 adsorption experiment.
[0084] Figure 6 The iodine adsorption performance of the three Im@DL229 materials prepared in Examples 1-4.
[0085] Figure 7 The iodine adsorption performance of the four types of Im_0.075@DL229 and DL229 prepared in Example 3.
[0086] from Figure 6-Figure 7 It can be seen that the Im_0.075@DL229 prepared in Example 3 has the best iodine adsorption effect, with an adsorption amount of up to 9.8 g / g, which is 1.9 times higher than that of the DL229 material before modification (adsorption amount of 5.2 g / g).
[0087] Figure 8The iodine adsorption kinetics experimental results of Im_0.075@DL229 and DL229 prepared in Example 3. It can be seen that the iodine adsorption of Im_0.075@DL229 increases rapidly in the first 8 hours, the adsorption curve is basically linear, and the adsorption curve tends to equilibrium after 24 hours. The adsorption rate of iodine by the Im_0.075@DL229 sample is significantly higher than that of DL229.
[0088] Effect Verification Example 2 Iodine Retention Test
[0089] Three different methods were used to test iodine retention. The small open bottles containing the Im@COF samples at iodine adsorption equilibrium were placed in three empty large bottles (100 ml). The three large bottles were sealed, half-opened, and fully opened at room temperature (corresponding to three different environments: closed environment, semi-closed environment, and open environment). The small bottles containing the samples were weighed every 24 hours and then placed back in the empty large bottles for continued desorption.
[0090] Fig. 9 The iodine retention test results of DL229 and four Im@DL229 materials prepared in Examples 1-4 in a closed environment (room temperature conditions).
[0091] Fig.10 The iodine retention test results of DL229 and four Im@DL229 materials prepared in Examples 1-4 in a semi-closed environment (room temperature conditions).
[0092] Fig.11 The iodine retention test results of DL229 and four Im@DL229 materials prepared in Examples 1-4 in an open environment (room temperature conditions).
[0093] Combination Figure 9-11 It can be seen that the iodine retention rate of the Im@DL229 material loaded with imidazole is higher than that of the single COF sample, and the improvement is more obvious in semi-closed and open environments.
[0094] Effect Verification Example 3 Material Regeneration Test
[0095] The composite COF material adsorbing iodine or CH3I is regenerated by ethanol treatment to release the adsorbed iodine or CH3I: the sample after absorbing iodine or CH3I is immersed in ethanol and ultrasonically tested for a certain period of time until the ethanol is colorless. The regenerated composite COF sample is reloaded with imidazole and reabsorbs iodine or CH3I.
[0096] Fig.12 This is the iodine desorption curve (75°C) of Im_0.075@DL229 synthesized in Example 3. It can be seen that the adsorbed iodine is released rapidly in the first 2 hours, then slowly, and finally reaches desorption equilibrium within 11 hours. Finally, 70% of the adsorbed iodine is released.
[0097] Fig.13 The results of five consecutive static iodine adsorption cycles of Im_0.075@DL229 and DL229 synthesized in Example 3. The results show that after five cycles, the iodine adsorption capacity of DL229 is only about 40% of the original; while Im_0.075@DL229 still maintains the original iodine adsorption capacity, indicating that the imidazole loading effectively retains the recovery capacity of the adsorbent.
[0098] Fig.14 These are the experimental results of CH3I adsorption performance of Im_0.075@DL229 and DL229 synthesized in Example 3.
[0099] Fig.15 These are the static CH3I adsorption kinetic experimental results (75°C) of Im_0.075@DL229 synthesized in Example 3.
[0100] Figure 14-15 The results showed that the adsorption of CH3I by Im_0.075@DL229 after loading with imidazole increased from 0.75 g / g to 1.28 g / g, an increase of 70%. In addition, the adsorption rate of CH3I by Im_0.075@DL229 was very fast, reaching adsorption equilibrium within the first 4 hours.
[0101] Fig.16 This is a static CH3I cyclic adsorption experiment of Im_0.075@DL229 synthesized in Example 3. The results show that after 5 cycles, the adsorption amount of CH3I by Im_0.075@DL229 remains basically unchanged.
[0102] Fig.17 The CH3I retention experimental results (room temperature conditions) of Im_0.075@DL229 synthesized in Example 3 in three different environments (closed environment, semi-closed environment, and open environment). The results show that the CH3I retention effect of Im_0.075@DL229 under different conditions is above 94%, showing a good retention effect.
[0103] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a covalent organic framework composite material loaded with imidazole, characterized in that: The following steps are involved: The imidazole is loaded by using the covalent organic framework material DL229 to obtain the imidazole loaded covalent organic framework composite material.
2. The method for preparing the imidazole-loaded covalent organic framework composite material according to claim 1, characterized in that: The mass ratio of the covalent organic framework material DL229 and imidazole is (0.8-0.2):
1.
3. The method for preparing the imidazole-loaded covalent organic framework composite material according to claim 1, characterized in that: The load temperature is 120° C. and the load time is 24-72 hours.
4. The method for preparing the imidazole-loaded covalent organic framework composite material according to claim 1, characterized in that: The covalent organic framework material DL229 is obtained by reacting 1,3,5,7-tetrakis(4-aminophenyl)adamantane and terephthalaldehyde as monomers at 100°C.
5. The method for preparing the imidazole-loaded covalent organic framework composite material according to claim 4, characterized in that: The reaction time is 1-3 days.
6. The method for preparing the imidazole-loaded covalent organic framework composite material according to claim 4, characterized in that: The molar ratio of the 1,3,5,7-tetrakis(4-aminophenyl)adamantane to terephthalaldehyde is 9:
1.
7. The imidazole-loaded covalent organic framework composite material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the imidazole-loaded covalent organic framework composite material as claimed in claim 7 as an iodine adsorbent.
Citation Information
Patent Citations
Application of imidazole / metal organic framework composite material
CN115382343A
